2017
DOI: 10.5114/aoms.2017.69326
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering nutraceuticals in clinical practice: position paper from an International Lipid Expert Panel

Abstract: Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide, reaching 31% of deaths in 2012 [1]. In particular, atherosclerosis and ischemic heart disease (IHD) are the main causes of premature death in Europe and are responsible for 42% of deaths in women and 38% in men under 75 years old [2]. The global economic impact of CVD is estimated to have been US $906 billion in 2015 and is expected to rise by 22% by 2030 [3]. Cardiovascular diseases also represent the major cause of disability in dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
227
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 261 publications
(235 citation statements)
references
References 267 publications
4
227
0
4
Order By: Relevance
“…Of note, the important role of curcumin in a clinical setting was recently reviewed by an International Lipid Panel expert [98]. In this work, the authors concluded that an evidence-based approach to the use of lipid-lowering nutraceuticals could improve the quality of the treatment, including therapy adherence, and achievement of the LDL-C goal in clinical practice, an important endpoint in cardiovascular disease [99][100][101][102].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 97%
“…Of note, the important role of curcumin in a clinical setting was recently reviewed by an International Lipid Panel expert [98]. In this work, the authors concluded that an evidence-based approach to the use of lipid-lowering nutraceuticals could improve the quality of the treatment, including therapy adherence, and achievement of the LDL-C goal in clinical practice, an important endpoint in cardiovascular disease [99][100][101][102].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 97%
“…[29][30][31][32] However, products containing RYR can cause adverse effects, 22 therefore, in order to limit them, before taking any nutraceutical, several factors must be considered, such as the components contained in the blend and their dosage, the dosage of RYR and the amount of MK. MK is the most important molecule among monacolins produced by the fermentation of red rice by the yeast Monacus purpureus; it has a molecular structure similar to lovostatin, 16 the precursor of an entire class of statin drugs considered the elective treatment of dyslipidemia and cholesterol control. The ability of monacolin K to act on cholesterol biosynthesis by reducing the function of HMG-CoA reductase as a competitive inhibitor is now known, and many studies have been conducted on several NCs containing RYR with different dosages of monacolin K to study its efficacy and/or safety in hypercholesterolemic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in recent years, research interest has been focusing on the possible lipid-lowering effects of red yeast rice (RYR) supplements, 5,13,14 so that their use is recommended in the ESC/ EAS guidelines and international documents. 3,15,16 RYR is produced by fermentation of white rice by the mold fungus Monacus purpureus that, by its fermenting activity, enriches the rice of a group of substances called monacolines, which possess a marked and scientifically proven hypocholesterolemic activity. Among them, monacolin K (MK), which has a structure identical to levostatin, 17 inhibits the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase, a key enzyme in cholesterol biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Moreover, a growing preclinical literature suggests that BBR has a broad number of antinfective activities, [9][10][11] and it could also exert some protective effects against neurodegenerative processes. [2][3][4][5][6][7][8] Moreover, a growing preclinical literature suggests that BBR has a broad number of antinfective activities, [9][10][11] and it could also exert some protective effects against neurodegenerative processes.…”
Section: Source and Biological Function Of Berberinementioning
confidence: 99%